Formation and decay of radicals during Vacuum-UV irradiation of poly(dimethylsiloxane). (October 2017) - Schilinsky, Laura; Jeschke, Gunnar; Tschaggelar, René; Wilken, Ralph; Klose, Daniel
Abstract: Formation of radicals in a poly(dimethylsiloxane) (PDMS) elastomer upon 172 nm vacuum-UV (VUV) irradiation was investigated by electron paramagnetic resonance spectroscopy (EPR). Kinetics of radical buildup and decay was investigated under varying conditions and found to depend strongly on the degree of pre-modification of the polymer. Furthermore, radicals were observed only when oxygen was absent during in situ VUV irradiation. The EPR spectrum is dominated by a broad signal, assignable to unspecified carbon-centered radicals. Stationary radical concentrations during VUV irradiation in nitrogen atmosphere can reach 0.2 mol/L in an about 260 nm thick surface layer, consistent with the remaining carbon concentration in the modified PDMS as measured by XPS. Gas diffusion is not limiting kinetics of the modification process. Our findings are consistent with a mechanism where oxygen molecules from the atmosphere diffuse in PDMS and quench radical sites in the polymer.